The The Correlation Between Total Cholesterol Levels In Pregnancy Women And Baby Birth Weight - uliyatul laili; Rizki Amalia (Universitas Nahdlatul Ulama Surabaya, 2021)
Maternal nutritional intake during pregnancy will affect the process of fetal growth and development, including intake of cholesterol levels. The fetus obtains amino acids and fatty acids through the placental absorption mechanism of maternal cholesterol. Cholesterol levels in pregnant women are needed by the fetus to meet fetal cholesterol during organogenesis. The purpose of this study was to determine the relationship between total cholesterol levels in pregnant women and birth weight. The research method used was a prospective cohort. This research was conducted at the Endang Sidoarjo Maternity Home from June to August 2020. The sample in this study was 33 respondents in the third trimester of pregnancy, the sample was taken by purposive sampling. The independent variable in this study was total cholesterol levels while the dependent variable was birth weight. Cholesterol levels are obtained based on the results of measurements with digital tools while birth weight is measured using baby scales. The results showed as many as 22 respondents with normal cholesterol levels gave birth to fetuses weighing 2500-4000 grams. Based on the results of data analysis with the statistical test, the p value was obtained p value 0.137> 0.05. The conclusion of this study is that there is no relationship between total cholesterol levels in pregnant women and birth weight.